Oxygen Reduction Reaction at Penta-Coordinated Co Phthalocyanines - Viera, Marco; Riquelme, Jorge; Aliaga, Carolina; Marco, José F.; Orellana, Walter; Zagal, José H.; Tasca, Federico (Frontiers in Chemistry, 2020)
From the early 60s, Co complexes, especially Co phthalocyanines (CoPc) have been extensively studied as electrocatalysts for the oxygen reduction reaction (ORR). Generally, they promote the 2-electron reduction of O2 to give peroxide whereas the 4-electron reduction is preferred for fuel cell applications. Still, Co complexes are of interest because depending on the chemical environment of the Co metal centres either promote the 2-electron transfer process or the 4-electron transfer. In this study, we synthetized 3 different Co catalysts where Co is coordinated to 5 N atoms using CoN4 phthalocyanines with a pyridine axial linker anchored to carbon nanotubes. We tested complexes with electro-withdrawing or electro-donating residues on the N4 phthalocyanine ligand. The catalysts were characterized by EPR and XPS spectroscopy. Ab initio calculations, Koutecky– Levich extrapolation and Tafel plots confirm that the pyridine back ligand increases the Co-O2 binding energy, and therefore promotes the 4-electron reduction of O2. But the presence of electron withdrawing residues, in the plane of the tetra N atoms coordinating the Co, does not further increase the activity of the compounds because of pull-push electronic effects.